DAMPAK METODE PELATIHAN TERHADAP PENGETAHUAN DAN KOMPETENSI PESERTA PELATIHAN PERKESMAS BAGI KOORDINATOR PERKESMAS DI WILAYAH PROVINSI JAWA TENGAH DAN JAWA TIMUR - Arif Rahmat Kurnia; Febrina Suci Hati (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
The Public Health Nursing Service (Perkesmas) Training for Perkesmas Coordinators at Public Health Centers (Puskesmas) is a program to revitalize Perkesmas activities at Puskesmas. The training used blended learning (BL) and completed online learning (FOL) methods. This observational study used a comparative descriptive method with a quantitative approach. The study aims to determine the impact of FOL and BL methods on the knowledge and competence of participants in Perkesmas training. A purposive sampling method was used to select 176 participants, and data collection was conducted using standardized instruments. The data analysis included univariate and bivariate. The normality test used the Kolmogorov-Smirnov test, and the comparative test used the Mann-Whitney test. There were significant differences (p <0.05) in knowledge, as indicated by the post-test scores, Perkesmas activity planning scores (MI 1), and average competency scores between trainees who received FOL compared to those who received BL. In conclusion, there was a significant difference in the knowledge and competence of participants in Public Health Training for Public Health Coordinators who received FOL compared to those who received BL. This research is helpful for policymakers and training providers to select the most effective training methods to increase trainees' knowledge.